The Development of the Curriculum: Theoretical Insights and Practical Preconditions - Žadeikaitė, Loreta; Zaleskienė, Irena (Pedagogika, 2016)
The article discusses the research insights of professor Bronislovas Bitinas towards change of curriculum and practicalities of his implementation, towards change in education paradigm. Authors of the article analyse the research heritage of professor which is fully publicized into “Selected Works in Education by Bronius Bitinas” (I–III t., 2013). The main points from Selections are disclosed in article in order to show the continuity of his theoretical ideas, the preconditions for practical realization of these ideas, the innovativity of the developments in the curriculum change for the national as well as for international educational community. Realization of the ideas of B. Bitinasarelinked with the steps in national educational Reform, with developments and improvements of educational interaction at different levels. Besides that the positive role of professors ideas and insights for development of the new acts and regulations in education, for improvement of school activities are discussed by the authors of the article. After analyzing theoretical and practical approaches of B. Bitinas, authors of the articles state some conclusions: the research based pedagogical insights of professor B. Bitinas are still very actual for nowadays education: political decisions, the development of acts for implementation of the curriculum, etc. are still based upon his theoretical ideas and practical assumptions. As a result of research by summarising the ideas the statement is made about sustainability of professor’s insights and ideas into three major streams: Curriculum theory, Research based Curriculum and Social context of education. Authors suggest to go forward in researching these streams.